Biosynthesis of silver nanoparticles (AgNPs) from coconut leaf extract and their antifungal activity against Ganoderma boninense mycelia - Gusti Ayu Dewi Lestari; I Gusti Ayu Made Megayanti; Komang Ayu Astuti Maharani; Ni Wayan Nieskajanti Kedeh Van Kempen (Menara Perkebunan, 2024)
Basal stem rot disease caused by Ganoderma is a major problem in palm cultivation in Indonesia, so an appropriate solution is needed to overcome this problem. One of the solutions that can be applied is through silver nanoparticles. Synthesis of silver nanoparticles can use coconut leaves as a source of flavonoids. Flavonoids are one of the phenolic compounds that are widely used in the process of synthesizing silver nanoparticles. Flavonoid compounds have a hydroxyl group (OH), which can be reduced by donating electrons to the Ag+ ion from AgNO3 to Ag0. This research aims to synthesize silver nanoparticles (AgNPs) using coconut leaf water extract and its assessment as an antifungal for Ganoderma boninense. Silver nanoparticles were synthesized by mixing coconut leaf extract in 1 mM of AgNO3 solution with a ratio of 1:9 (v/v). The concentrations of coconut leaf water extract were 1% and 3% with a heating temperature of 60°C. Silver nanoparticles were characterized using a UV-Vis spectrophotometer, PSA, FTIR, TEM, and SEM-EDS. The AgNPs had a maximum wavelength of 430 nm, with morphologies like a ball, triangle, and square, a mass percentage of Ag of 51.77%, smallest particle size of 63.29 nm, PdI value of 0.3361, and a zeta potential of -16.98 mV. The FTIR spectra show that the functional group that plays a role in the reduction process is the –OH group. The antifungal activity assay produced the highest percentage of colony growth inhibition (68.37%) at a concentration of 4.9 ppm in the 10-day incubation.